2001
DOI: 10.1111/j.1741-3737.2001.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Contexts of Time to First Sex Among Hispanic Adolescents

Abstract: This investigation examines the sociocultural influences on risk of first sex among a representative sample of Hispanic (primarily of Mexican origin) teens living in Los Angeles County. Teen acculturation (measured as language of interview) moderates the effects of gender on risk of sex, with less acculturated teens exhibiting the greatest gender difference. Teens living with both biological parents have significantly lower risk of sex and the effect of family acculturation (measured as generational status) op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 42 publications
9
82
1
Order By: Relevance
“…Negative self-perception of academic achievement was associated with risky behavior and problematic outcomes such as early coital debut and unwanted pregnancy Upchurch, Aneshensel, & Mudgal, 2001), while school attendance and school achievements were associated with later intercourse (Kirby, 2002). Religious affiliation of adolescents correlated with sexual debut at an older age (Meier, 2003;Paikoff et al, 2000;Pedersen et al, 2003).…”
Section: Personal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative self-perception of academic achievement was associated with risky behavior and problematic outcomes such as early coital debut and unwanted pregnancy Upchurch, Aneshensel, & Mudgal, 2001), while school attendance and school achievements were associated with later intercourse (Kirby, 2002). Religious affiliation of adolescents correlated with sexual debut at an older age (Meier, 2003;Paikoff et al, 2000;Pedersen et al, 2003).…”
Section: Personal Factorsmentioning
confidence: 99%
“…For example, Pedersen et al (2003) found that parental education level affected boys' coital debut but not girls', while others found that parental socioeconomic status, including overall educational level, was related to coital debut Resnick et al, 1997;Valle, Torgersen, Roysamb, Klepp, & Thelle, 2005). Fractured family structure (e.g., living with one parent or in a reconstituted family) was reported to be associated with early coital debut Kirby, 2002;Upchurch et al, 2001).…”
Section: Interpersonal Interactions: Family and Peersmentioning
confidence: 99%
“…Indeed, several studies have found negative effects of assimilation (particularly acculturation) on certain outcomes for immigrant adolescents. For example, assimilation is reported to be related to early or risky sexual behavior (Harris 1999;Landale and Hauan 1996;Upchurch et al 2001) and higher risks of delinquency and substance abuse (Harris 1999;Nagasawa et al 2001;Zhou and Bankston 1998). Rumbaut (1997) also cites prior research showing detrimental effects of assimilation on adolescents' educational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for males to be more sexually active than females may be a manifestation of Latino cultural values, such as machismo and marianismo, which prescribe traditional gender roles (Schuster, 2003). Machismo is a concept that describes the male role as dominant, independent, and protective of the family, whereas marianismo refers to the female role as a caregiver, a virgin, and obedient to men (Gloria, Ruiz, & Castillo, 2004;Upchurch et al, 2001). Men are allowed sexual freedom, while women are expected to maintain their virginity (Schuster, 2003).…”
mentioning
confidence: 99%